Prognostic Factors for Paediatric Abdominal Trauma at Tertiary Care Center - Shinde, Nandkishor; Baseer, Mohammed Abdul Baseer1; Devani, Ravindra G Devani; Manjunath J, (Iranian Journal of Pediatric Surgery, 2023)
Introduction: Paediatric abdominal trauma incidence increasing due to rising population, industrialization, modernization, increase in the vehicular traffic, terrorist activities and riots. This study is done to know the prognostic factors in paediatric abdominal trauma which help in decreasing morbidity and mortality. Material and Methods: This retrospective study was conducted at a tertiary care centre, from May 2016 to April 2022. Retrospectively records of all the paediatric patients with a history of abdominal trauma were analysed from case files. Demographic data, mode of injury, mechanism of injury, nature of the injury, definitive treatment and outcome of patients were analysed. Results: There were 110 paediatric abdominal trauma patients. Road traffic accidents was the most common mode of trauma seen in 70% of cases, followed by fall which comprises25.5% cases. 25 (22.7%) cases were hemodynamically unstable on presentation.70 (63.6%) cases required transfusion of blood or blood products. Penetrating abdominal trauma was seen in 19 (17.3%) cases, while blunt trauma seen in 91 (82.7%) cases, most common solid organ of injury was spleen seen in 46 (41.8%) cases, Surgical interventions were required in 29(26.4%) cases, however 81(73.6%) cases were managed conservatively. All patients of traumatic bowel perforation required surgical intervention. Nine (08.1%) patients were succumbed to death. Among the factors leading to mortality, delayed presentation (78%), hemodynamic instability (89%), requirement of transfusion (100%), penetrating abdominal trauma (78%), higher grade injury (67%), surgical interventions (89%) were commonly identified and were poor prognostic factors. Conclusion: Delayed presentation, hemodynamic instability, penetrating abdominal trauma, higher grade of injury, surgical intervention are the poor prognostic factors. Site of injury, mechanism and the mode of injury are other factors contributing and deciding prognosis in paediatric abdominal trauma.